The Effects of ESG and Institutional Quality on Financial Stability: Evidence from GCC Banks - Almulla, Saeed; Albaity, Mohamed; Al-Tamimi, Hussein A. Hassan (International Journal of Economics and Financial Issues, 2025)
The objective of this study is to explore the effect of Environmental, Social, and Governance (ESG) practices, and institutional quality on banks financial stability in the Gulf Cooperation Council (GCC) region for the period from 2010 to 2023. To achieve this, the study utilizes a Generalized Quantile Regression (GQR) on a sample of 33 GCC banks. The regression analysis assesses the influence of ESG measured by ESG score, and institutional quality, measured using an index of the average of six core aspects of governance “voice and accountability, political stability and absence of violence, government effectiveness, regulatory quality, rule of law, and control of corruption” on banks financial stability. We measure financial stability using the Z-score and the Standard Deviation of Return on Assets (SDROA), we employ eight control variables in our analysis “Bank Size, Deposits, Solvency, Equity, Competition, ROE, Islamic banks, GDP, Inflation, and Oil Rents” Our findings reveal that ESG scores positively impact bank stability, while institutional quality has a negative effect. Our findings suggest key policy actions to regulators and policy maker to enhance bank stability.